Tradisi Saweran Terhadap Qori’ Al-Qur’an: Studi Analisis Tafsir Maqashidi Pada QS. Al-A’raaf [7]: 204 - Jamaluddin, Hanif (Jurnal Studi Islam dan Sosial, 2023)
This article examines the saweran tradition of reciting the Qur’an using the Tafsir Maqāṣid approach initiated by Abdul Mustaqim. The tradition of saweran against Qur'ānic reciters is usually done by pelted, and even tucked with money into the clothes of a reciter who is chanting the holy verses of the Qur'ān by spectators or worshippers. This is widely found in an event commemorating Islamic holidays. In QS. al-A'rāf [7]: 204 it has been explained that when the Qur'ān is recited, listen and listen so that you understand the verses it contains and take the lessons it conveys. Based on this verse, the commentators agreed to prohibit the transfer of money to the readers of the Qur'ān for various reasons, but when viewed in terms of the overall opinion of the commentators leads that the tradition of saweran towards the Qur'ānic reciter is not in accordance with the rules in listening to the Qur'ān. However, by using the Tafsir Maqāṣid approach the results of the interpretation are not only limited to prohibiting the recitation of the Qur'ān, but also produce the main intention or message behind the QS. al-A'rāf [7]: 204. If viewed from  the Maqāṣid, namely ḥifẓ al-Dīn, ḥifẓ al-Māl, ḥifẓ al-Nafs, and ḥifẓ al-Dawlah Saweran tradition against the Qur'ānic qāri’  has the potential to tarnish the sanctity of Islam and the glory of the Qur'ān and its readers, like to show off wealth (flexing), degrading the dignity of a Qur'ān qāri’ , and including sexual harassment.